PENGARUH PENGUMUMAN PENERBITAN SAHAM SYARIAH TERHADAP RETURN SAHAM PT SMART, TBK DAN PT ASTRA INTERNATIONAL, TBK - Putri adelia. Putri; Fitria Nailal Khilda; Silvi Amelia Febriyani; Ibnu Muttaqin (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2022)
This study aims to analyze the effect of Islamic stock issuance on stock returns before and after issuance. The population in this study id the share of the issuer PT Smart Tbk and PT Astra International Tbk which are listed on the Indonesia Stock Exchange (IDX) in the period 2019 and 2020. The sample in this study was obtained by purposive sampling, namely with a total sample of 60 days before and after. This study uses secondary data recorded in quantitative data in the form of announced share prices at PT Smart Tbk ang PT Astra International Tbk wich are listed on Indonesia Stock Exchane Website (Bursa Efek Indonesia, 2018) and also data on closing price of shareson a Yahoo Finance website. The analiytical method used is the paired sample t-test using SPSS 26. The Results of this study indicate that: (1) Announcement of the issuance of shares in PT Smart Tbk it has no significant effect on changes in stock returns, it is proven that there is no correlation between the two return data before and after being registered at ISSI. (2) Announcement of the issuance of shares in PT Astra International Tbk has no effect on changes in stock return, it is shown that there is no relationship between the two return data before and after being removed from ISSI.